Systematic Literature Review and Bibliometric Analysis Seafarer Supply and Demand - Fahmi Umasangadji; Rizki Wijaya; Nafi Almuzani (Dinasti International Journal of Education Management And Social Science, 2024)
This study conducts a systematic assessment of the literature and does a bibliometric analysis to investigate the fluctuations in the availability and need for seafarers in the marine sector. The study examines a diverse selection of publications from several subfields within the seafarer workforce domain, analysing significant patterns, difficulties, and opportunities for enhancement. The study provides insights into the scholarly landscape of seafarer workforce research by analyzing highly cited articles, prolific authors, and influential journals. The findings highlight the significant impact of technological advancements, demographic shifts, regulatory changes, and economic factors on seafarer supply and demand dynamics. The systematic review and bibliometric analysis offer valuable information for policymakers, industry stakeholders, researchers, and academicians seeking to understand and address the complexities of the seafarer workforce. The initial review of articles obtained from the pilot search informed the formulation of research questions to understand the current state, trends, impactful studies, influential authors, and areas for future exploration within the seafarer workforce literature. Keywords related to seafarers and workforce were identified and refined through a three-step process to create an optimal set of search terms. This systematic literature review has provided valuable insights into various aspects of the seafarer workforce, including trends, challenges, and potential areas for future research. By employing a rigorous methodology and analyzing relevant literature, this study contributes to the ongoing discourse on seafarer supply and demand dynamics, offering a foundation for informed decision-making and further exploration in this field.